Factors Influencing Acceptance of ILMU E-Learning Among Lecturers: An Empirical Study Based on UTAUT Model - Safitri, Eristya Maya; Amalia, Indira Setia; Mukaromah, Siti; Faroqi, Asif (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
E-learning is a form of innovation in technology used in educational field, including higher education. University of Pembangunan Nasional “Veteran” Jawa Timur is one of many universities that have implemented e-learning called ILMU to support the teaching-learning process. The application of ILMU as e-learning has yet to be utilised by lecturers, due to some challenges in implementation of ILMU regarding accessibility and features of ILMU. Meanwhile, successful implementation of a technology requires acceptance from its users. This research was acquited to define what acceptance factors that influence lecturers while accessing ILMU. This study is measured using UTAUT model. The research was carried on by quantitatively distributing questionnaires to 60 lecturers. Data were analyzed and processed using SEM-PLS technique and SMARTPLS 3.0 application. Factors that influence users to receive ILMU e-learning and significantly are effort expectancy, social influence, facilitating conditions, and behavioral intention. Meanwhile, performance expectancy does not influence users significantly to accept ILMU e-learning. These factors are key indicators to of the implementation and improvement of ILMU e-learning, thus it will develop a better implementation for the lecturers to use and accept it.